Belize. Significant achievements 2014 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2016)
The main activities carried out by the Institute in Belize during 2014 are identified, with respect to the needs and interests of the country, identifying problems in adaptive technologies for family farming, climate change, food security, . Likewise, among the achievements carried out, the advances of the different projects implemented, the extension activities in dissemination of information with publications, forums, training and research are recognized.